ANALISIS PERAN ETIKA ADMINISTRASI DALAM OPTIMALISASI KUALITAS LAYANAN PUBLIK DI KANTOR KELURAHAN TANJUNGREJO MALANG - Zulkarnaen, Akhmad Ivan; Sofian, Octa Dwi (JOURNAL AKSES STIA MALANG, 2025)
Abstract Administrative ethics plays a strategic role in determining the quality of public services, which should not only focus on fulfilling administrative needs but also reflect key principles such as justice, equality, accountability, loyalty, and social responsibility. These principles serve as a critical foundation for realizing good governance, particularly at the village (kelurahan) level as the frontline of public service delivery. This study is intended to analyze the role of administrative ethics in optimizing the quality of public services at the office of Tanjungrejo urban village in Malang City, focusing on four main dimensions: equality, justice, loyalty, and responsibility. A descriptive qualitative approach was employed, using observation, interviews, and documentation techniques, with the village head, structural officials, and community members as informants. The findings indicate that the application of ethics in the dimensions of equality and justice has been carried out optimally through services that follow procedures and are free from discrimination. Employee loyalty is generally well demonstrated, although issues of discipline remain. Meanwhile, the majority of staff show a strong sense of professional responsibility in carrying out their duties. These findings affirm that the consistent implementation of administrative ethics can significantly improve the effectiveness and quality of public services, while also strengthening accountability and public trust in local government institutions.